Separation of conjoined twins from the common law and Shari'ah perspectives: the legal and ethical conundrum - Jahn Kassim, Puteri Nemie; Alias, Fadhlina (International Institute of Islamic Civilisation and Malay World (ISTAC), International Islamic University Malaysia (IIUM), 2018)
The birth of conjoined twins is a comparatively rare event, constituting 1 in 100,000 births. Being a product of a single fertilised egg, these twins are believed to be the result of an incomplete division of embryo, which inhibits complete development of various organ systems. As a result, they usually suffer from physical malformation manifested in for instance, conjoined hearts, lungs, livers, limbs or even genito-urinary tracts. Thus, their chronic medical condition tends to require surgical intervention. However, separating them triggers a plethora of legal and ethical issues as separation may involve the possibility of sacrificing one twin if they are sharing organs. This inevitably creates a range of ethical dilemmas, particularly, in choosing between sanctity of life and quality of life as the survival of one twin threatens the life of the other. In certain circumstances, separation may not lead to the demise of the other but may cause severe harm to the other or a possible hazard to at least one twin’s cognitive outcome. Nevertheless, in spite of their physical attachment, the twins are legally and morally distinct and are different individuals with competing needs and interests. Legal issues arising from the separation of conjoined twins such as criminal liability, parental autonomy and the determination of the “best interests” criterion has been the subject of much debate in courts. Thus, this research paper seeks to discuss the legal and ethical issues arising from the separation of conjoined twins from the common law and shari’ah perspectives.